Implementation of Hospital Absolute Responsibility in Health Services in Indonesia (Universitas Negeri Semarang (UNNES), 2022)
Doctors and patients are a legal relationship in a business agreement (inspanning verbintenis) and not an outcome agreement (resultaat verbintenis). Even so, the doctor is still responsible for any negligence that brings harm to the patient. Until now, there is still confusion in Indonesia, whether medical liability is based on default or tort, although as an inspanning verb, a more appropriate basis for lawsuits to use is tort. This research was conducted by making a comparison of law with statutory approaches, conceptual approaches and case approaches. An analysis of absolute liability cases in Indonesia is needed to provide justice for the community, especially in health law.